Indonesian Marketplace: Factors in Purchasing Decisions and Impact on Sales - Chikita Putri Prameswari; Zahra Hafizha Isaura; Osly Usman (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The current development has made everything switch to digital form, one of which is in business in Indonesia. Currently, many marketplaces have followed the times to be able to survive in the many marketplace competitions that occur in Indonesia. To maintain it, the marketplace needs to identify influences in increasing its sales. This research discusses the influence of live streaming commerce, influencer marketing, discounts, online customer reviews, on purchasing decisions and their impact on sales in the Indonesian marketplace. This research uses quantitative research methods that collect data by distributing questionnaires to marketplace users. Then the data is processed to determine the relationship between one relationship and another. With this research, it is hoped that it can be a consideration for the marketplace in Indonesia for the sustainability of its business.